Applying traceability to grinding circuits by using Particle Texture Analysis (PTA) - Oghazi, Pejman; Pålsson, Bertil; Tano, Kent (Luleå tekniska universitet, Industriell miljö- och processteknik, 2008)
LKAB has started a new pelletizing plant at Malmberget, where the raw material will be a mix of ores from Kiruna and Malmberget. The new plant necessitated an investment in a new grinding section in the concentrator. As usual, the new section has larger mills. It also lacks the wet cobbing stage present in the old sections.Comparing the results from the new section with the old sections show that they give similar results. There are slight variations; the older mills produce a steeper final particle size distribution. Also, it appears that the new mills are more efficient, since they have higher calculated grindability indices.To better understand the differences between the sections, and the process implications of the new grinding section, a combination of Particle Texture Analysis (PTA) and the statistical method Multivariate Analysis (MVA) is used. It shows that it is possible to identify and follow systematic changes in the particle morphology of the mill products. Also, that there are differences between the old and new grinding sections. Godkänd; 2008; 20081113 (cira)